Malignant peripheral nerve sheath tumour (MPNST) of mandible: solving the perplexity. (11th March 2015) - Patel, Shilpa; Pathak, Jigna; Dekate, Kamlesh; Mohanty, Neeta
Abstract : We present an extremely rare case of malignant peripheral nerve sheath tumour (MPNST) in a 30-year-old woman without associated neurofibromatosis 1. The patient presented with an 8 cm×4 cm lesion extending from 46 to the retro molar region involving the ramus of the right mandible associated with regional paraesthesia. Incisional biopsy revealed spindle cells with vesicular nuclei arranged in fascicles leading to a diagnosis of spindle cell lesion. Posterior segmental mandibulectomy was performed under general anaesthesia. On excisional biopsy, a definitive diagnosis of low-grade MPNST was established on the basis of immunohistochemistry. The patient was then lost to follow-up.